Morphology, paradigms, and periphrases - Anderson, John M. (John Mathieson), 1941- (Oxford : Oxford University Press, 2011)
This volume is concerned with the role of the lexicon, in particular its inflectional morphology, in mediating between syntax and phonology. It examines the expressive role of inflection and the notion of grammatical periphrasis and what these reveal about the substantive differences between verbs and nouns.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Grammar, Comparative and general -- Morphology; Grammar, Comparative and general -- Phonology; Paradigm (Linguistics); Periphrasis